2022
DOI: 10.3389/fphar.2022.931282
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of key biomarkers for the early diagnosis of diabetic kidney disease

Abstract: Background: Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease. This study explored the core genes and pathways associated with DKD to identify potential diagnostic and therapeutic targets.Methods: We downloaded microarray datasets GSE96804 and GSE104948 from the Gene Expression Omnibus (GEO) database. The dataset includes a total of 53 DKD samples and 41 normal samples. Differentially expressed genes (DEGs) were identified using the R package “limma”. The Metascape database was subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Using the GSE96804 database, research determined that THBS2, COL1A2, COL6A3, and CD44 might be potential biomarkers and treatment prospects for DKD ( 45 ). Finally, about GSE104948, scientists used this database for bioinformatics analysis and experimental verification identified three novel DKD-specific genes ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using the GSE96804 database, research determined that THBS2, COL1A2, COL6A3, and CD44 might be potential biomarkers and treatment prospects for DKD ( 45 ). Finally, about GSE104948, scientists used this database for bioinformatics analysis and experimental verification identified three novel DKD-specific genes ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oligoadenylate synthetase 1 (OAS1) has been found to mediate apoptosis of thymic pre-T-cells and to be associated with auto-in ammatory immunode ciency [42]. Moreover, multiple reports have con rmed that OAS1 is a key biomarker for the diagnosis of diabetic nephropathy and a hub gene for lupus nephritis and chronic kidney disease [43][44][45]. Radical S-adenosyl methionine domain-containing protein 2 (RASD2) expression is closely related to the degree of differentiation of podocytes, and its regulatory expression gradually decreases with the development of the kidney [46].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to explore the regulatory mechanisms of differentially signi cant genes and their regulatory mechanisms, we conducted small RNA sequencing on corresponding samples [51][52][53], including the affected child, their sibling, and their parents. We quanti ed the expression levels of microRNAs (miRNAs) and performed Weighted Gene Co-expression Network Analysis (WGCNA) [37,54] (Figures S5A-S5D and Table S5). Our results revealed that miRNAs were divided into 14 modules (de ned as densely interconnected clusters of genes) (Fig.…”
Section: Mir378c-mediated Regulation Of Ptpn14 Promotes the Activatio...mentioning
confidence: 99%